Hybrid precoding using long-term channel statistics for massive MIMO systems - Sungwoo Park; Jeonghun Park; Heath, Robert W.; Yazdan, Ali (Proceedings of the ... IEEE International Conference on Acoustics, Speech and Signal Processing (1998), 2017)
Hybrid analog/digital precoding in the downlink of multiuser massive MIMO systems can reduce the number of RF chains hence reducing total cost and improving power efficiency. Having few RF chains, however, makes it difficult for a base station to acquire instantaneous channel state information across all antennas. We develop a hybrid technique that uses only long-term (slowly changing) channel statistics in computing the analog precoding matrix. The proposed analog precoder is designed to maximize signal-to-leakage-plus-noise ratio (SLNR) when combined with a baseband precoder. We also propose a constrained precoder design that reduces the effect of a hardware constraint where the analog precoders are realized with phase shifters.